Impact of COVID-19 on the imaging diagnosis of cardiac disease in Europe. Issue 2 (5th August 2021) - Williams, Michelle Claire; Shaw, Leslee; Hirschfeld, Cole B; Maurovich-Horvat, Pal; Nørgaard, Bjarne L; Pontone, Gianluca; Jimenez-Heffernan, Amelia; Sinitsyn, Valentin; Sergienko, Vladimir; Ansheles, Alexey; Bax, Jeroen J; Buechel, Ronny; et al.
Abstract : Objectives: We aimed to explore the impact of the COVID-19 pandemic on cardiac diagnostic testing and practice and to assess its impact in different regions in Europe. Methods: The online survey organised by the International Atomic Energy Agency Division of Human Health collected information on changes in cardiac imaging procedural volumes between March 2019 and March/April 2020. Data were collected from 909 centres in 108 countries. Results: Centres in Northern and Southern Europe were more likely to cancel all outpatient activities compared with Western and Eastern Europe. There was a greater reduction in total procedure volumes in Europe compared with the rest of the world in March 2020 (45% vs 41%, p=0.003), with a more marked reduction in Southern Europe (58%), but by April 2020 this was similar in Europe and the rest of the world (69% vs 63%, p=0.261). Regional variations were apparent between imaging modalities, but the largest reductions were in Southern Europe for nearly all modalities. In March 2020, location in Southern Europe was the only independent predictor of the reduction in procedure volume. However, in April 2020, lower gross domestic product and higher COVID-19 deaths were the only independent predictors. Conclusion: The first wave of the COVID-19 pandemic had a significant impact on care of patients with cardiac disease, with substantial regional variations in Europe. This has potential long-term implications for patients and plans are required to enable the diagnosis of non-COVID-19 conditions during the ongoing pandemic.